“Between Primitive Hut and Large Scale Housing: The Present of Utopia in Architecture” - Seng, Eva- Maria (Scottish Journal of Arts, Sciences and Scientific Studies)

Artistik und Zirkus als immaterielles Kulturerbe. Was macht eine künstlerische Leistung zum immateriellen Kulturerbe? - Seng, Eva- Maria (Politik und Kultur. Zeitung des Deutschen Kulturrates)

Johann Georg Starcke - Seng, Eva- Maria (Neue Deutsche Biographie Bd. 25)

Rekonstruktion des religiösen Ortes - Seng, Eva- Maria (Die Welt und ihr Double. Abriss und Rekonstruktion, Bauhaus Lectures (im Druck))

Die Vereine für christliche Kunst und die Bildausstattung der Kirchen nach dem 2. Weltkrieg in Westfalen und Württemberg im Vergleich - Seng, Eva- Maria (Kultbild und Andachtsbild)

"Kulturerbe zwischen Globalisierung und Lokalisierung“ - Seng, Eva- Maria (Europäisches Kulturerbe. Bilder, Traditionen, Konfigurationen)

Ehrenpromotion der Fakultät für Kulturwissenschaften der Universität Paderborn an Herta Müller. Paderborn, 29.10.2012. Dokumentation

„Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur

„Wenn ihr zufrieden seid, so ist’s vollkommen“. Vom Hof in Ferrara zur Villa Massimo in Rom oder: Der Autor im Betrieb - Eke, Norbert Otto (Poetiken der Gegenwart. Deutschsprachige Romane nach 2000)

Zu „sagen […], ich unterschreibe Alles, Hunde sind wir ja doch!‘ halte ich des Mannes, des Christen unwürdig“ – Zivilcourage im Vormärz - Eke, Norbert Otto (Jahrbuch zur Liberalismus-Forschung 25)

„Südliches Meer“. Rausch und Ekstase in Gottfried Benns Werk - Eke, Norbert Otto (Benn Forum Band 3 2012/13. Beiträge zur literarischen Moderne [Jahrbuch])

‚Macht nichts, macht nichts, sagte ich mir, macht nichts‘: Herta Müller’s Romanian Novels - Eke, Norbert Otto (Herta Müller)

Widerstehen und Widersprechen [Laudatio auf Herta Müller] - Eke, Norbert Otto (Ehrenpromotion der Fakultät für Kulturwissenschaften der Universität Paderborn an Herta Müller. Paderborn, 29.10.2012. Dokumentation)

„Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur - Eke, Norbert Otto („Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur)

Geklebte Strukturen im Fahrzeugbau – Simulation und Bewertung von Fertigungstoleranzen - Kruschinski, Georg; Matzenmiller, Anton; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson (Leichtbau-Technologien im Automobilbau)

Simulation und Bewertung von Fertigungstoleranzen - Kruschinski, Georg; Matzenmiller, Anton; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artoem; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Georg; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (ACS Nano)

Low-Voltage Self-Assembled Monolayer Field-Effect Transistors on Flexible Substrates - Schmaltz, Thomas; Amin, Atefeh Y.; Khassanov, Artoem; Meyer-Friedrichsen, Timo; Steinrück, Hans-Georg; Magerl, Andreas; Segura, Juan José; Voitchovsky, Kislon; Stellacci, Francesco; Halik, Marcus (Advanced Materials)

Oxygen diffusivity in silicon derived from dynamical X-ray diffraction - Will, J.; Gröschel, A.; Kot, D.; Schubert, M. A.; Bergmann, C.; Steinrück, Hans-Georg; Kissinger, G.; Magerl, A. (Journal of Applied Physics)

Experimentieren lernen auf Englisch - geht das? - Ein bilingual ausgerichtetes Chemieprojekt zur Vermittlung des Erkenntniswegs im Film - Fechner, Sabine; Schüttler, Susanne (MNU)

Konzeption und Inbetriebnahme einer neuen Technikumsanlage zur Absorption und Desorption von CO2 - Hüser, Nicole; Kenig, Eugeny

Kartellrecht der Kreditwirtschaft (Syst. VI) - Krimphove, Dieter (Kölner Kommentar zum Kartellrecht Bd. 4)

Kartellrecht der Versicherungswirtschaft (Syst. VI) - Krimphove, Dieter (Kölner Kommentar zum Kartellrecht Bd. 4)

Eigene Innovation oder Zugangsberechtigung zu fremden Innovationen - Krimphove, Dieter (Handbuch Innovationsmanagement)

Ökonomisch/juristische Konzeption der Innovationen - Krimphove, Dieter (Handbuch Innovationsmanagement)

AT 5 der MaComp: Zusammenarbeit mehrere Wertpapierdienstleistungsunternehmen - Krimphove, Dieter (Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen)

AT 7 der MaComp: Das Verhältnis §§ 33 WpHG ff. zu § 25a KWG - Krimphove, Dieter (Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen)

Brain activity in predictive sensorimotor control for landings: an EEG pilot study. - Baumeister, Jochen; von Detten, S; van Niekerk, SM; Schubert, M; Ageberg, E; Louw, QA (Int J Sports Med)

Instrumented anterior mobilization of the ankle joint increases contralateral somatosensory cortex activation in healthy subjects - Needle, AR; Swanik, CB; Schubert, M; Reinecke, K; Higginson, JS; Baumeister, Jochen

Quelltextgenerierung für LEGO Mindstorms-Roboter - Geismann, Johannes (Berichtsband der Informatiktage 2013: Smarte Sichten, smarte Schichten)
Die Komplexität von mechatronischen Systemen wird stetig größer. MechatronicUML (MUML) ist eine Methode zur Entwicklung für Software von mechatronischen Systemen. Im Rahmen einer Bachelorarbeit wurde ein bestehender Quelltextgenerator für MUML-Modelle so erweitert, dass Quelltext für ein Echtzeitbetriebssystem generiert werden kann, welches auf einem LEGO Mindstorms-Roboter installiert ist.

Determinants of market beta: the impacts of firm-specific accounting figures and market conditions - Schlueter, Tobias; Sievers, Sönke (Review of Quantitative Finance and Accounting (VHB-JOURQUAL 3 Ranking B))
This article examines and extends research on the relation between the capital asset pricing model market beta, accounting risk measures and macroeconomic risk factors. We employ a beta decomposition approach that nests competing models with different business risk proxies and allows to frame cross-model comparison. Because model tests require estimated independent variables resulting in measurement error, we empirically estimate three comparable model specifications with instrumental variable estimators and for the first time provide thorough instrument diagnostics in this setting. Correcting for the heretofore neglected weak instruments problem we find that growth risk (i.e., the risk of firm sales variations that are inconsistent with the market wide trends), is the business risk that explains cross-sectional variations in market beta best.
Keywords: CAPM; Cost of capital; Accounting beta; Intrinsic business risk; Growth risk; Instrumental variables

Play-out for Hierarchical Component Architectures - Holtmann, Jörg; Meyer, Matthias (Proceedings of 11th Workshop Automotive Software Engineering)
One approach to cope with the growing complexity of today’s embedded systems software, especially in the automotive domain, is component-based software development. For systems based on hierarchical component architectures like AUTOSAR and developed in conformance with process models such as Automotive SPICE, requirements should be specified for the whole system under development and partitioned subsequently onto the particular components across several hierarchy layers. In previous work, we developed a formal requirements engineering (RE) approach based on a recent Live Sequence Chart (LSC) variant, so-called Modal Sequence Diagrams (MSDs). This scenario-based RE approach allows to validate the requirements by means of simulation (i.e., the play-out algorithm originally conceived for LSCs) and to formally verify the requirements for consistency. However, these scenarios are specified on a plain structural basis that does not reflect the typical structure of component architectures, which are arranged in a hierarchical way and encompass ports, interfaces, and directed connectors. In order to tackle this problem, we introduce in this paper a modeling and simulation approach for MSDs based on hierarchical component architectures. By binding these two aspects together, we foster an integrated and iterative RE and component architecture design.

Modulare Leistungsprognose von Kompaktsteuerungen - Frieben, Jens; Heutger, Henning; Meyer, Matthias; Becker, Steffen (9. Paderborner Workshop Entwurf mechatronischer Systeme)

Sichere Speicherung vertraulicher Daten in verteilten Versionskontrollsystemen - Lass, Michael
Distributed revision control is widespread throughout the software industry. Systems like git and mercurial gained a lot of users over the last years and started to supersede central systems like Subversion or CVS in some projects. While restricting access to those central systems is basically possible, it is difficult to control the propagation of contents in a distributed revision control system because every user has a local copy of the whole repository. In this thesis a concept is developed and implemented that allows secure storage of confidential data in a distributed revision control system and enables users to manage read and write permissions on single confidential files. Therefore different cryptographic methods are used, such as asymmetric encryption, digital signatures and convergent encryption. These techniques are applied in a manner that fits the special requirements of a revision control system and allows a space efficient storage of changes to the encrypted files.

An evaluation testbed for adaptive, topology-aware deployment of elastic applications - Keller, Matthias; Robbert, Christoph; Peuster, Manuel (Proceedings of the ACM SIGCOMM 2013 conference on SIGCOMM)

CROWD: An SDN Approach for DenseNets - Ali-Ahmad, Hassan; Cicconetti, Claudio; de la Oliva, Antonio; Draxler, Martin; Gupta, Rohit; Mancuso, Vincenzo; Roullet, Laurent; Sciancalepore, Vincenzo (2013 Second European Workshop on Software Defined Networks)

A Scalable Redundant TDMA Protocol for High-Density WSNs Inside an Aircraft - Blanckenstein, Johannes; Garcia-Jimenez, Javier; Klaue, Jirka; Karl, Holger (Lecture Notes in Electrical Engineering)

Cliquenbildung in verteilten Systemen - Blumentritt, Fritz

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, P.; Graffi, K. (2013 Conference on Networked Systems)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks -- Workshops)

Denser Networks for the Future Internet, the CROWD Approach - de la Oliva, Antonio; Morelli, Arianna; Mancuso, Vincenzo; Draexler, Martin; Hentschel, Tim; Melia, Telemaco; Seite, Pierrick; Cicconetti, Claudio (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)

Enzyklopädie Erziehungswissenschaft Online - Medienpädagogik

Medienpädagogik in Institutionen der Erwachsenen- und Weiterbildung - Kamin, A.-M.; Meister, Dorothee M. (Enzyklopädie Erziehungswissenschaft)

Vermittlung von Medienkompetenz in der Praxis für Kinder und Jugendliche: Schule - Meister, Dorothee M. (Medienkompetenzförderung für Kinder und Jugendliche. Eine Bestandsaufnahme)

Anforderungen an das Lesen in der digitalen Mediengesellschaft - Gerhardts, L.; Meister, Dorothee M. (Zukunft des Lesens. Was bedeuten Generationswechsel, demografischer und technischer Wandel für das Lesen und den Lesebegriff?)

Spiele als Lernköder? Über das Potenzial von Computerspielen - Ganguin, S.; Meister, Dorothee M. (Kinder-Eltern-Medien. Medienpädagogische Anregungen für den Erziehungsalltag)

Medienpädagogische Anregungen für den Erziehungsalltag – Einführende Gedanken - Kamin, A.-M.; Meister, Dorothee M.; Schulte, D. (Kinder- Eltern-Medien)

Lithium niobate dielectric function and second-order polarizability tensor from massively parallel ab initio calculations - Riefer, Arthur; Rohrmüller, Martin; Landmann, Marc; Sanna, Simone; Rauls, Eva; Vollmers, Nora Jenny; Hölscher, Rebecca; Witte, Matthias; Li, Yanlu; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (High Performance Computing in Science and Engineering ‘13)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe–Salpeter equation yield a dielectric function for the stoichiometric material that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are at least partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that self-energy effects improve the agreement between experiment and theory. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular for the 21 and 31 tensor components, further improving the agreement with measured data.

HOMO band dispersion of crystalline rubrene: Effects of self-energy corrections within the GW approximation - Yanagisawa, Susumu; Morikawa, Yoshitada; Schindlmayr, Arno (Physical Review B)
We investigate the band dispersion and relevant electronic properties of rubrene single crystals within the GW approximation. Due to the self-energy correction, the dispersion of the highest occupied molecular orbital (HOMO) band increases by 0.10 eV compared to the dispersion of the Kohn-Sham eigenvalues within the generalized gradient approximation, and the effective hole mass consequently decreases. The resulting value of 0.90 times the electron rest mass along the Γ-Y direction in the Brillouin zone is closer to experimental measurements than that obtained from density-functional theory. The enhanced bandwidth is explained in terms of the intermolecular hybridization of the HOMO(Y) wave function along the stacking direction of the molecules. Overall, our results support the bandlike interpretation of charge-carrier transport in rubrene.

A material-based quality concept for polymer laser sintering - Josupeit, Stefan; Rüsenberg, Stefan; Schmid, Hans-Joachim (24th Annual International Solid Freeform Fabrication Symposium)
In this work, the quality of laser sintered parts is investigated along a defined process chain for a nylon 12 material (PA 2200) on an EOSINT P395 laser sintering system. Important influencing factors are figured out. Rheological powder characterization methods are investigated as well as mechanical, physical and other chosen part properties. The concept allows reproducible part quality characteristics and is used to obtain (testing) temperature dependent material data. It can also be extended on further materials based on nylon 12: PA 2241 FR, which is convenient for the aircraft industry due to its flame-retardant properties, and PA 2221, which has economic advantages due to a lower material consumption.